2007
DOI: 10.1007/s00442-007-0868-y
|View full text |Cite
|
Sign up to set email alerts
|

Stem respiration and carbon dioxide efflux of young Populus deltoides trees in relation to temperature and xylem carbon dioxide concentration

Abstract: Oxidative respiration is strongly temperature driven. However, in woody stems, efflux of CO(2) to the atmosphere (E (A)), commonly used to estimate the rate of respiration (R (S)), and stem temperature (T (st)) have often been poorly correlated, which we hypothesized was due to transport of respired CO(2) in xylem sap, especially under high rates of sap flow (f (s)). To test this, we measured E (A), T (st), f (s) and xylem sap CO(2) concentrations ([CO(2)*]) in 3-year-old Populus deltoides trees under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 44 publications
3
68
0
5
Order By: Relevance
“…Similarly strong correlation was observed also in other studies (e.g. Zha et al, 2004;Saveyn et al, 2008). That infers that stem temperature is a main factor driving CO 2 effl ux from stems.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly strong correlation was observed also in other studies (e.g. Zha et al, 2004;Saveyn et al, 2008). That infers that stem temperature is a main factor driving CO 2 effl ux from stems.…”
Section: Discussionsupporting
confidence: 71%
“…Maier and Clinton, 2006;Teskey and McGuire, 2005) the relationship between CO 2 effl ux and CO 2 concentration in xylem was observed. Saveyn et al (2008) observed a signifi cant increase in stem CO 2 concentration during rain. He explained that as a result of an increase in cell respiration and stopping sap fl ow which would transport the CO 2 off .…”
Section: Discussionmentioning
confidence: 93%
“…Stem CO 2 efflux was based on the volume (V in m 3 ) of the stem sector behind the chamber (i.e. living tissue of bark and sapwood) and coarse root CO 2 efflux on the totally enclosed coarse root volume, respectively (Desrochers et al, 2002;Saveyn et al, 2008). …”
Section: Assessment Of Stem and Coarse Root Co 2 Effluxmentioning
confidence: 99%
“…Por ejemplo, en el trabajo de McGuire y Teskey (2004), la albura de Platanus occidentalis exhibía un flujo axial en las horas centrales del día en que la transpiración era máxima muy superior al registrado durante 24 h (103 mmol CO 2 m -3 s -1 ), es decir un 71 % de la respiración estimada a partir del balance de masa entre el flujo axial, radial y de almacenamiento del CO 2 . Igualmente, Saveyn et al (2008) observaron que el flujo axial en Populus deltoides Bartr. ex Marsh.…”
Section: Transporte Axial De Counclassified